The shopping activities in Melaka UNESCO World Heritage Site: local community benefited? = Aktiviti membeli-belah di Melaka UNESCO World Heritage Site: adakah komuniti setempat mendapat manfaat? - Ab Rahman, Syakir Amir; Mahamod, Lukman Hakim; Jaafar, Samsuddin (Selangor International Islamic University College, 2019)
Tourism is a significant sector to boost the local economic development with its strength to offer the economic sources to the destination. However, to date, there has been no discussion on the local economic in cultural heritage destinations in Malaysia. This study examined tourists’ expenditure on shopping sector, and its contribution to the local economic in Melaka UNESCO World Heritage area. A total of 1000 questionnaire survey were collected. Inferential analysis was used to identify the expenditure pattern of domestic and international tourist and its contribution to the local economy. The results revealed that the shopping sector recorded the third highest expenditure and were benefited to the local economy.